Forests and water : (Food and Agriculture Organization og the United Nations, 2008)
The availability and quality of clean water in many regions of the world is more and more threatened by overuse, misuse and pollution. in this context, the relationship between forests and water must be accorded high priority. This study, initiated in the context of the Global Forest Resources Assessment 2005, highlights the need for holistic management of complex watershed ecosystems taking into account interactions among water, forest and other land uses as well as socio-economic factors. it explains the role of forests in the hydrological cycle, with a particular focus on critical, 'red flag' forest situations such as mountainous or steep terrain, river and coastal areas and swamp ecosystems, as well as the special case of mountainous small islands.